Modeling a Rumor Propagation in Online Social Network: An Optimal Control Approach - Rachid Ghazzali; Amine El Bhih; Adil El Alami Laaroussi; Mostafa Rachik (Discrete Dynamics in Nature and Society)
We propose to model the phenomenon of the spread of a rumor in social networks in this paper. From an existing SIR model, we manipulate a new one that is based on the model of cholera in order to take into account professional pages that specialize in spreading rumors. In the second part, we introduce a control strategy to fight against the diffusion of the rumor. Our main objective is to characterize the three optimal controls that minimize the number of spreader users, fake pages, and the corresponding costs. For that matter, using the maximum principle of Pontryagin, we prove the existence and we give characterization of our controls. Numerical simulations are given to concretize our approach.